Tanggung Jawab Instansi Terkait Terhadap Peredaran Obat Impor Tradisional Kaitannya Dengan Perlindungan Konsumen (Studi Terhadap Obat Yang Tidak Terdaftar Di Kota Pontianak) - CHENDI WULAN SARI, SH. A.21209039, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2015)
AbstractDrug is a substance that is consumed by the body to reduce pain and eliminate thedisease . Medication can be useful to cure the kinds of diseases suffered by humans . Inthe present development , the drug can be divided into 2 groups , namely TraditionalMedicine and modern medicine . Article 106 of Law No. 36 of 2009 states that thepharmaceutical preparations and medical devices can only be released after obtaining amarketing authorization.Based on the description of the background , issues to be addressed in this studyare as follows , How oversight of imported traditional medicine in Indonesia ?, HowLegal responsibilities of imported traditional medicine importers in Indonesia ? and Howto remedy the negative impact of imported traditional medicine circulation withoutpermission on ? Research the law can be divided into normative legal research and legalresearch soiologis . The legal research used in this thesis is a normative legal research isresearch that is done by examining library materials which are also called secondary dataand legal research literature . Factor is the juridical legislation ( Act No. 8 of 1999 onConsumer Protection ) , whereas the empirical factor is effort related agencies in order toprevent the circulation of imported drugs without a marketing authorization.The results of the study , each drug and food imports into Indonesia is overseen bya body called the National Agency of Drug and Food of the Republic of Indonesia ( FDA- RI ) . If we are keen to see the products and medicinal foods we consume from a foreigncountry , usually in packs contained no FDA - RI Registration Number . Given thesenumbers , it is clear that the food or medications that we purchase has been approved bythe FDA - RI . In order to keep an eye on any food and drug in Indonesia , FDA - RI hasissued a regulation , known as Regulation of the Head of Drug and Food ControlRepublic of Indonesia Number HK.00.05.1.3459 on Drug Importation ImportSupervision and Regulation of Food and Drug Monitoring Agency number :HK.03.1.23.10.11.08481 2011 on Criteria and Procedures for drug Registration , abusiness agents in the course of import of traditional medicine has a good faith obligationin conducting its business activities , provide information that is correct , clear and honestabout the condition and security of goods and / or services as well as member ofexplanation use , repair and maintenance , treat or serve customers properly and honestly2and not discriminatory , Ensure quality of drugs produced and / or traded under theprovision of quality standard of goods and / or services are applicable , provide anopportunity to the consumers to test and / or try the goods and / or services as well asprovide a guarantee and / or warranty on goods produced and / or traded , givingcompensation , compensation and / or reimbursement for damages resulting from the use, consumption and use of goods and / or services traded , Giving compensation , damagesand / or replacement if the goods and / or services received or not used in accordancewith the agreements . Remedies Negative Impact Of Imported Traditional Without DrugsCirculation Marketing Authorization is through the court and out of court SettlementSuggested Need for awareness of the authorities to conduct surveillance andmore intensive examination of the circulation of imported traditional medicine as hasbeen mandated in the legislation governing it so that no consumers who feel aggrievedKeywords: Imported Traditional Medicines, without marketing authorization andConsumer ProtectionAbstrakObat merupakan zat yang dikonsumsi tubuh untuk mengurangi rasa sakit maupunmenghilangkan suatu penyakit. Obat dapat berguna untuk menyembuhkan jenis-jenispenyakit yang diderita oleh manusia. Pada perkembangan sekarang ini, obat dapat dibagimenjadi 2 kelompok, yakni Obat Tradisional dan obat modern. Pasal 106 Undang-Undang Nomor 36 Tahun 2009 menyatakan bahwa Sediaan farmasi dan alat kesehatanhanya dapat diedarkan setelah mendapat izin edar. Bertitik tolak dari uraian latarbelakang, masalah yang akan dibahas pada penelitian ini adalah sebagai berikut,Bagaimana mekanisme pengawasan atas peredaran obat tradisional impor di Indonesia?,Bagaimanakah tanggung jawab importir dalam importasi obat tradisional ke dalamwilayah hukum Republik Indonesia ? dan Bagaimana upaya hukum dari Instansi terkaitterhadap dampak negatif peredaran obat tradisional impor tanpa izin edar? Penelitianhukum dapat dibedakan menjadi penelitian hukum normatif dan penelitian hukumsoiologis. Adapun penelitian hukum yang digunakan dalam thesis ini adalah penelitianhukum normatif yaitu penelitian yang dilakukan dengan cara meneliti bahan pustakayang merupakan data sekunder dan disebut juga penelitian hukum kepustakaan. Faktoryuridisnya adalah peraturan perundang-undangan (Undang-undang RI Nomor 8 Tahun1999 tentang Perlindungan Konsumen), sedangkan mengenai faktor empirisnya adalahupaya instansi terkait dalam rangka mencegah peredaran obat impor tanpa izin edar.Hasil penelitian, Pengawasan yang dilakukan Badan POM terdiri 2 bentuk, yaituPre market dan Post Market, Seorang pelaku usaha dalam menjalankan kegiatan imporobat tradisional mempunyai kewajiban Beritikad baik dalam melakukan kegiatanusahanya, Memberikan informasi yang benar, jelas dan jujur mengenai kondisi danjaminan barang dan/atau jasa serta member penjelasan penggunaan, perbaikan danpemeliharaan, Memperlakukan atau melayani konsumen secara benar dan jujur sertatidak diskriminatif, Menjamin mutu obat yang diproduksi dan/atau diperdagangkanberdasarkan ketentuan standar mutu barang dan/atau jasa yang berlaku, Memberikankesempatan kepada konsumen untuk menguji dan / atau mencoba barang dan / atau jasatertentu serta memberi jaminan dan / atau garansi atas barang yang dibuat dan/atau yangdiperdagangkan, Memberi kompensasi, ganti rugi dan/atau penggantian atas kerugianakibat penggunaan, pemakaian dan pemanfaatan barang dan/atau jasa yang3diperdagangkan, Memberi kompensasi, ganti rugi dan / atau penggantian apabila barangdan / atau jasa yang diterima atau dimanfaatkan tidak sesuai dengan perjanjian. UpayaHukum Dari Dampak Negatif Peredaran Obat Impor Tradisional Tanpa Izin Edar yaitumelalui pengadilan dan Penyelesaian di luar pengadilan Disarankan Perlu adanyakesadaran dari pihak yang berwenang untuk melakukan pengawasan dan pemeriksaanyang lebih intensif terhadap peredaran obat tradisional impor sebagaimana yang telahdiamanatkan dalam peraturan perundang-undangan yang mengatur mengenai hal tersebutsehingga tidak ada lagi konsumen yang merasa dirugikan.Kata kunci: Obat Tradisional Impor, tanpa izin edar dan Perlindungan Konsumen.